Disruption of endocytic trafficking in frontotemporal dementia with CHMP2B mutations - Urwin, Hazel (Oxford University Press, 2010)
Mutations in CHMP2B cause frontotemporal dementia (FTD) in a large Danish pedigree, which is termed FTD linked to chromosome 3 (FTD-3), and also in an unrelated familial FTD patient. CHMP2B is a component of the ESCRT-III complex, which is required for function of the multivesicular body (MVB), an endosomal structure that fuses with the lysosome to degrade endocytosed proteins. We report a novel endosomal pathology in CHMP2B mutation-positive patient brains and also identify and characterize abnormal endosomes in patient fibroblasts. Functional studies demonstrate a specific disruption of endosome–lysosome fusion but not protein sorting by the MVB. We provide evidence for a mechanism for impaired endosome–lysosome fusion whereby mutant CHMP2B constitutively binds to MVBs and prevents recruitment of proteins necessary for fusion to occur, such as Rab7. The fusion of endosomes with lysosomes is required for neuronal function and the data presented therefore suggest a pathogenic mechanism for FTD caused by CHMP2B mutations.